DevOps for Azure Applications Deploy Web Applications on Azure - Machiraju, Suren (Apress, 2018)
Deploy web applications on Azure using DevOps tools. This book gives solutions to real-world Cloud deployment scenarios which will enable you to become adept in DevOps work for Azure. You'll start by seeing an overview of DevOps for Azure deployments where you will also survey the available tools, including Octopus Deploy and TeamCity. Here, you will learn how to use TeamCity as a CI tool and Octopus Deploy as release-management and CD software to get your package deployed on Azure Web Application. Next, the authors demonstrate using the Microsoft Visual Studio Team Services (VSTS) integrated developer platform. Finally, you will go through some real-world scenarios using DevOps tools to deploy web applications on Azure. To do this, you will create resources in Azure and integrate with an open source buildout. After reading this book, you will be ready to use various tools in a DevOps environment to support an Azure deployment. You will: Carry out a survey of DevOps tools Build a DevOps solution using standalone DevOps tools - TeamCity and Octopus Deploy Use an integrated DevOps platform - VSTS Build out an Azure deployment using open source code and VSTS.